Lip prints – an aid in sex identification - Roy, Saurabh; Yadav, Karnika; Jha, Manisha (Journal of Chitwan Medical College, 2024)
Background: The grooves existing on human lips are exclusive to every individual and can be used to determine individuality. Lip prints are regular lines and fissures in the arrangements of wrinkles and grooves present in the zone of transition of human lip, between the inner labial mucosa and outer skin, examination of which is recognized as cheiloscopy. Cheiloscopy is a forensic investigation technique that deals with the identification of human based on the lip prints. Method: The present descriptive cross-sectional study was conducted in Nobel Medical College and Teaching Hospital, Biratnagar, Nepal. The data were collected by performing cheiloscopic collection. Participants included students of Bachelor of Dental Surgery in the college who agreed. Exclusion criteria were deformity, infection of the lips. Ethical approval was obtained. The lip prints were analyzed according to Suzuki and Tsuchihashi classification. Statistical analysis was carried out by using SPSS 20, descriptive statistics like mean and percentage were analyzed. The X2 test was used to compare types of prints and gender. A p<0.05 was considered statistically significant. Result: There were total of 103 participants, age ranging from 18 to 25 years. Type 1 prints were common, and Type 3 least common. Type 2 lip print was more in males and Type 1 in females. The difference in various types of lip prints between male and female was not statistically significant. Conclusion: The study showed that lip print is unique, Type 1 is common, and more males have Type 2 pattern. The sex of the person can be foretold on the basis of patterns present in prints.